Free‐volume nanostructural transformation in crystallized GeS2–Ga2S3–CsCl glasses: Freie‐Volumen nanostrukturelle Umwandlung in kristallisierten GeS2–Ga2S3–CsCl Gläsern. Issue 2 (26th January 2016) - Klym, H.; Ingram, A.; Shpotyuk, O.
Abstract : The free‐volume nanostructural transformation in fully crystallized (80GeS2 –20Ga2 S3 )100–x (CsCl)x, x = 0; 5; 10; 15 chalcogenide glasses was studied by positron annihilation lifetime spectroscopy using mixed positron‐ and positronium‐trapping modes. The CsCl content in GeS2 –Ga2 S3 glassy matrix changed the defect‐related component in positron lifetime spectra and confirmed the structural void agglomeration in comparison with the base glass. A larger amount of CsCl in (80GeS2 –20Ga2 S3 )85 (CsCl)15 glass resulted in void fragmentation due to loosening of the structure. "Pure" positron‐positronium modes calculated by a decomposition formalism show that a realistic process is connected with the expansion of voids formed as a consequence of CsCl addition and complete crystallization into the inner structure of glasses. The CsCl additive formed new positron‐trapping sites in the Ge–Ga–S glassy matrix. The bulk positron lifetime in glasses corresponded to positron trapping occurring in nanocrystalline particles. Interface voids were not particularly large because the characteristic value of 0.27–0.30 ns can be connected with typical free volumes of mono‐ and di‐vacancies.